Karbi Grammar - Jeyapaul, V.Y. (Central Institute of Indian Languages Mysore, 1987)
Karbi is the language of Assam. This is karbi language grammar book. In this book karbi language grammar and composition is included.
Keywords: Karbi; Inut Pherangke Akido; Grammar; Karbi; Karbi